2002
DOI: 10.1089/089771502753460222
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effect of Spinal Cord Injury and Functional Impairment on Human Brain Activation

Abstract: Reorganization of human brain function after spinal cord injury (SCI) has been shown in electrophysiological studies. However, it is less clear how far changes of brain activation in SCI patients are influenced by the extent of SCI (neuronal lesion) or the consequent functional impairment. Positron emission tomography ([15O]-H2O-PET) was performed during an unilateral hand movement in SCI patients and healthy subjects. SCI patients with paraplegia and normal hand function were compared to tetraplegic patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(70 citation statements)
references
References 30 publications
4
63
2
1
Order By: Relevance
“…tDCS mechanisms are related to its influence on sodium and calcium channels opening and NMDA receptors excitability [50], while longlasting effects are analogous to activity-dependent synaptic plasticity, namely long-term potentiation (LTP) and long-term depression (LTD) [51][52][53]. Structural, functional and connectivity alterations at the cortical level have been described in patients with SCI, especially in the somatosensory cortex, consequently to the injury itself, as well as a result of the lack of sensory and motor inputs [54][55][56]; these changes being related to neuropathic pain [57]. Therefore, it is possible that patients with SCI sustain a decline in plasticity mechanisms as compared to those observed in healthy subjects, and therefore, tDCS related neuroplastic mechanisms may occur in a delayed manner.…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%
“…tDCS mechanisms are related to its influence on sodium and calcium channels opening and NMDA receptors excitability [50], while longlasting effects are analogous to activity-dependent synaptic plasticity, namely long-term potentiation (LTP) and long-term depression (LTD) [51][52][53]. Structural, functional and connectivity alterations at the cortical level have been described in patients with SCI, especially in the somatosensory cortex, consequently to the injury itself, as well as a result of the lack of sensory and motor inputs [54][55][56]; these changes being related to neuropathic pain [57]. Therefore, it is possible that patients with SCI sustain a decline in plasticity mechanisms as compared to those observed in healthy subjects, and therefore, tDCS related neuroplastic mechanisms may occur in a delayed manner.…”
Section: Delayed Tdcs Effects On Pain Reductionmentioning
confidence: 99%
“…35 Not many studies have correlated the postoperative motor improvement with plasticity. 19 Some studies have shown adaptive changes in bilateral primary motor cortex (M1), supplementary motor area (SMA), premotor area (PMA), cingulate motor area, parietal cortex, and contralateral primary somatosensory cortex (S1) in cases of SCI [8][9][10][11][27][28][29]33,40 and cervical compressive myelopathy due to spondylosis. 13,14,23,38 In this study we aimed to understand the cortical changes that occur due to CSM and following CSM surgery and to correlate these changes with functional recovery by using functional MRI (fMRI).…”
mentioning
confidence: 99%
“…SCI is associated with complete or incomplete damage to ascending sensory and/or descending motor pathways [3,4] and may ultimately lead to alterations within neural circuits of M1 [5][6][7]. In controls, experimentally induced differentiation reduces inhibitory, GABAergic cortical activity in sensory motor cortices [8] and is a mechanism proposed to mediate rapid cortical plasticity [9].…”
Section: Introductionmentioning
confidence: 99%